2016
DOI: 10.1093/chemse/bjw058
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on Umami Taste

Abstract: The effect of temperature on umami taste has not been previously studied in humans. Reported here are 3 experiments in which umami taste was measured for monopotassium glutamate (MPG) and monosodium glutamate (MSG) at solution temperatures between 10 and 37 °C. Experiment 1 showed that for subjects sensitive to MPG on the tongue tip, 1) cooling reduced umami intensity whether sampled with the tongue tip or in the whole mouth, but 2) had no effect on the rate of umami adaptation on the tongue tip. Experiment 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Reducing bitterness to such low levels precluded measurement of bitter taste adaptation. A similar progressive effect of cooling at 10° and below was obtained in 2 recent studies of sweet and umami taste (Green and Nachtigal 2015;Green et al 2016). Because bitterness, sweetness and umami are all mediated by C-GPCRs, the thermal sensitivity of TRPM5 (Talavera et al 2005;Talavera et al 2007) must again be considered the possible source of these direct thermal effects.…”
Section: Effects Of Temperature Over Timesupporting
confidence: 67%
See 1 more Smart Citation
“…Reducing bitterness to such low levels precluded measurement of bitter taste adaptation. A similar progressive effect of cooling at 10° and below was obtained in 2 recent studies of sweet and umami taste (Green and Nachtigal 2015;Green et al 2016). Because bitterness, sweetness and umami are all mediated by C-GPCRs, the thermal sensitivity of TRPM5 (Talavera et al 2005;Talavera et al 2007) must again be considered the possible source of these direct thermal effects.…”
Section: Effects Of Temperature Over Timesupporting
confidence: 67%
“…Another aim was to investigate the effect of temperature on bitter taste adaptation. Recent studies from this laboratory have shown that temperature can affect both the initial taste intensity and the rate of taste adaptation in sweet taste (Green and Nachtigal 2015), whereas it affects only the initial intensity of umami taste (Green et al 2016). Because both sweet and umami taste are mediated by C-GPCRs, these results imply that whereas the TRPM5 hypothesis of thermal sensitivity of taste may be adequate to explain the effect of temperature on umami taste, it cannot explain the dual thermal effects on sweet taste.…”
Section: Introductionmentioning
confidence: 89%
“…After duplicates removal, abstract article record and backward searching yielded 169 articles. After full‐text record, a total of 111 articles remained for complete data extraction . Among them, we identified 23 studies as having a controlled protocol (including two studies with a randomisation process .…”
Section: Resultsmentioning
confidence: 99%
“…Saliva effects were assessed in 20 trials (Table ). The effect of temperature was studied within 19 trials (Table ), with the majority focusing on food temperature and four studies investigating oral thermal conditions as factor influencing taste . Fifteen studies pertained to the effects of addition of capsaicin, menthol or CO2 on taste (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation